Acute severe mitral regurgitation with cardiogenic shock caused by two-step complete anterior papillary muscle rupture during acute myocardial infarction - Hutyra, Martin; Skala, Tomas; Marek, Dan; Nemec, Petr; Sluka, Martin; Ostransky, Jiri; Richter, Marek; Lukl, Jan (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2006)
BACKGROUND: Rupture of a papillary muscle is an infrequent but often fatal mechanical complication of acute myocardial infarction. AIM: The aim of this paper is to present a case report of a 65-year old women with acute severe mitral regurgitation with cardiogenic shock caused by two-step complete anterior papillary muscle rupture during acute myocardial infarction. The transthoracic echocardiography was obtained at the bedside and showed a posterior mitral valve prolapse with a severe mitral regurgitation. During this examination the patient developed acute pulmonary oedema and a consequent cardiogenic shock. Transthoracic echocardiography was then reevaluated and completed. New findings of bi-leaflet mitral flail and progression of massive mitral regurgitation were documented. The complete rupture of a papilary muscle was then considered as a cause of an acute clinical deterioration. Intraoperative findings showed a complete transection of both heads of anterolateral and necrotic regions of basis of posteromedial papillary muscle. CONCLUSIONS: This case confirms the importance of immediate echocardiography in confirming a diagnosis of acute mechanical complications of acute coronary syndromes and this examination is important for the management of a hemodynamically unstable patient. Echocardiography should be done immediately on any patient in whom the diagnosis of mechanical complication of acute coronary syndromes is suspected.
Keywords: Humans; Mitral Valve Insufficiency; Papillary Muscles; ženské pohlaví; mitrální insuficience; Shock, Cardiogenic; senioři; Heart Rupture, Post-Infarction; Female; Aged; poinfarktová ruptura srdce; papilární svaly; kardiogenní šok; lidé; Acute Disease; akutní nemoc